PENINGKATAN RETENSI DAN BERPIKIR KRITIS MATERI SISTEM PENCERNAAN MELALUI PENGGUNAAN MEDIA TORSO PADA PEMBELAJARAN IPA SD - Miko Fitri Ana; Ach Barizi; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using torso media on improving students' memory and critical thinking skills in elementary school science learning, especially related to the digestive system material here. Torso media was chosen because it provides concrete visualization that helps students understand abstract concepts. This study uses an experimental method using 5th grade elementary school students as its subjects. Data were obtained through retention and critical thinking tests conducted before and after learning with torso media, as well as through observation during the learning process. The results showed that students who learned using torso media experienced a significant increase in memory and critical thinking skills. The use of torso media not only helps students retain information for a longer period of time, but also encourages them to be more active in asking questions, analyzing, and drawing conclusions. Therefore, torso media has proven to be an effective learning tool to improve students' memory and critical thinking skills related to the digestive system in elementary schools.